First records of bats (Mammalia: Chiroptera) from Muong Phang cultural and historical site, Dien Bien province, Northwestern Vietnam - Loi, Dao Nhan; Thong, Vu Dinh (Academia Journal of Biology, 2017)
The internationally renowned Muong Phang Cultural and Historical Site is located in the Dien Bien Phu region, northwestern Vietnam, and has received special attention from the public because of its great biodiversity. This site has a large forest area and other habitats including lakes, streams, rivers and paddyfield. These habitats would be ideal homes for bats and other biological taxa. However, in general, the wildlife of the Muong Phang Cultural and Historical Site receives little attention from scientists and authorities. Between 2014 and 2016, we conducted series of surveys for bats in Muong Phang. Bat capture and sound recordings were the main procedure to obtain materials and data necessary for the assessment of diversity and conservation status. The results of the surveys this time revealed that there are 19 species of bats belonging to 7 genera, 5 families in the study area. Of these, a Myotis sp. is different from all the previously recorded Myotis bats from Vietnam, and, a Rhinolophus sp. is different from every described species of the family Rhinolophidae. This paper provides the first records of bats from Muong Phang with remarks on their taxonomy and conservation status. Citation: Dao Nhan Loi, Vu Dinh Thong, 2017. First records of bats (Mammalia: Chiroptera) from Muong Phang cultural and historical site, Dien Bien province, Northwestern Vietnam. Tap chi Sinh hoc, 39(3): 296-302. DOI: 10.15625/0866-7160/v39n3.10641. *Corresponding author: vudinhthong@hotmail.com. Received 29 August 2017, accepted 10 September 2017